OP39 The association between an unhealthy childhood diet and body composition depends on prenatal experience: data from the southampton women's survey. (September 2018) - Crozier, SR; Baird, J; Inskip, HM; Harvey, NC; Robinson, SM; Cooper, C; Hanson, M; Godfrey, KM
Abstract : Background: The developmental mismatch hypothesis proposes that risk of diseases such as obesity is increased when impaired prenatal nutrition and growth, is followed by an unhealthy childhood diet. We used data from the Southampton Women's Survey (SWS) to investigate whether there was an interaction between conditional growth in fetal abdominal circumference (AC) in late pregnancy and diet at age 6 years on body composition at age 9 years. Methods: 3158 SWS women had live singleton births. AC was measured at 11, 19 and 34 weeks' gestation, birth, and ages 6 months and 1, 2, 3 and 6 years. At age 9 years a subset had dual-energy X-ray absorptiometry (DXA) scans. Among mothers with a reliable menstrual history, enabling precise gestation determination, 582 children had DXA measurements. Fat, lean and bone mass at age 9 years were transformed to z-scores. AC z-scores for age were created and conditional AC growth between each pair of consecutive time points calculated. At age 6 years a 'prudent' dietary pattern was identified using principal component analysis, characterized by frequent consumption of fruit, vegetables and fish. Linear regression models were fitted to assess effects of AC growth on 9-year body composition; a multiplicative interaction term for AC growth from 34 weeks to birth and 6 year prudent diet score was added. Confounding variables (determined by a Directed Acyclic Graph) were 9-year height, age at DXA, sex, breastfeeding duration, maternal BMI, education, smoking in pregnancy, late pregnancy vitamin D and pregnancy weight gain. Results: Greater AC growth z-scores from birth to 6 months, 2–3 years and 3–6 years were associated with higher fat mass and percentage fat at 9 years. The interaction between AC growth from 34 weeks to birth and 6 year prudent diet score was statistically significant for total fat (p=0.006) and percentage fat (p=0.005), but not for total lean or bone mass. Amongst children with low late gestation AC growth, lower prudent diet scores were associated with greater 9-year total and percentage fat, whereas amongst children with high AC growth in late gestation there was little effect of prudent diet score on total and percentage fat. Conclusion: Individuals showing late gestation faltering of fetal growth who then had an unhealthy imprudent childhood diet had greater adiposity, while childhood diet was less influential on adiposity in individuals whose fetal growth had not faltered, providing evidence in support of the mismatch hypothesis.